The hill we climb an inaugural poem for the country - Gorman, Amanda 1998- (Viking, 2021)
"On January 20, 2021, Amanda Gorman became the sixth and youngest poet, at age twenty-two, to deliver a poetry reading at a presidential inauguration. Her inaugural poem, "The Hill We Climb," is now available to cherish in this special edition." --
Keywords: Gorman, Amanda -- 1998- -- The hill we climb; United States / Social aspects / Poetry; Political poetry; Poetry